The influence of store atmosphere and service quality on purchase decisions at Muslimah store in Merauke Regency - Wenny Aniwandari; Florentina Blandina Parapaga; Dodhy Hyronimus Ama Longgy; Suddin Lada (Global Advances in Business Studies, 2026)
This study aims to examine the effect of store atmosphere and service quality on purchase decisions at Muslimah store, located in Kampung Harapan Makmur, Merauke Regency. The population in this research consists of end consumers who have made purchases at Muslimah store, with an unlimited and large population size. The sample of the study consists of 96 respondents, determined using Cochran’s formula and a purposive sampling technique based on specific criteria, such as having shopped within the last six months and having direct experience with the store atmosphere and staff service. This research applies a quantitative explanatory approach, utilizing both primary and secondary data. Data collection techniques include observation and the distribution of a Likert-scale questionnaire. Data were analyzed using SPSS version 25 through validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that the store atmosphere variable (X₁) has a positive and significant partial effect on purchase decisions (Y). The service quality variable (X₂) also has a positive and significant partial effect on purchase decisions (Y). The F-test shows that both store atmosphere and service quality simultaneously have a significant influence on purchase decisions. Therefore, it can be concluded that both partially and simultaneously, store atmosphere and service quality significantly affect purchase decisions at Muslimah store.